Antipermeability and antiproliferative effects of standard and frozen bevacizumab on choroidal endothelial cells. Issue 6 (19th December 2006) - Peters, Swaantje; Julien, Sylvie; Heiduschka, Peter; Grisanti, Salvatore; Ziemssen, Focke; Adler, Martin; Schraermeyer, Ulrich; Bartz-Schmidt, Karl-Ulrich
Abstract : Background: Bevacizumab is an antiangiogenic compound developed to target tumour vessels. Its off-label use in ophthalmology requires in vitro testing on ocular cells. Aim: To quantify the antipermeability and antiproliferative effects of bevacizumab on cultured choroidal endothelial cells (CECs). It was examined whether deep-freezing of bevacizumab attenuates its antiangiogenic activity. Methods: Porcine CECs were cultured in permeable insert systems. Permeability of the cell monolayers was quantified by a fluorescent isothiocyanate-dextran assay after treatment with vascular endothelial growth factor (VEGF; 20–100 ng/ml) alone and in combination with bevacizumab (0.1–1 mg/ml). Proliferation of the CECs was tested using a "wound scratch" assay. The experiments were repeated with bevacizumab after freezing at −20°C for 5 days. Results: Bevacizumab significantly reduced VEGF-induced permeability in a dose-dependant manner. A molar ratio of 2.6:1 of bevacizumab to VEGF was required for complete blocking of VEGF-induced rise in permeability. CEC proliferation was significantly blocked by bevacizumab (0.5 mg/ml). Thawed bevacizumab after deep freezing showed a moderate, but not statistically significant loss in activity. Conclusion: Bevacizumab significantly reduces VEGF-induced permeability and proliferation of CECs. Freezing and thawing of bevacizumab will affect its biological activity.